PENGARUH SIZE DAN DIGITAL BANKING TERHADAP ROE DENGAN BOPO SEBAGAI VARIABEL MEDIASI - Izza Afkarina; Idah Zuhroh; Eris Tri Kurniawati (Journal of Financial Economics & Investment, 2026)
This study analyzes the effect of SIZE and digital banking on ROE with BOPO as a mediating variable, with digital banking proxied by the adoption of digital services (electronic money). The research sample consists of 7 Category 4 banks registered with the OJK with complete quarterly financial reports for the 2021–2024 period, yielding 112 observations. The analysis method used Structural Equation Modeling (SEM). The research results show that the mediation test indicates that operational efficiency does not mediate the relationship between bank size and profitability, while digital banking mediates the relationship between bank size and operational efficiency, but does not mediate the relationship between bank size and profitability. These findings indicate that the contribution of digital banking is more dominant in increasing operational efficiency than its direct impact on profitability, thus requiring a sustainable digitalization strategy to support long-term financial performance.